2020
DOI: 10.1108/ijqss-02-2020-0028
|View full text |Cite
|
Sign up to set email alerts
|

Different role of hotel CSR activities in the formation of customers’ brand loyalty

Abstract: Purpose Given the important role of corporate social responsibility (CSR) to enhance company performance, the purpose of this paper is to fill the existing gaps in the hotel CSR literature via application of the loyalty formation mechanism and conceptualizations of different aspects of CSR initiatives. Design/methodology/approach The current study examines the effect of environmental and social CSR strategies on multidimensional brand loyalty of hotel customers (i.e. cognitive, affective and conative). This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 82 publications
0
22
0
Order By: Relevance
“…Finally, a moderator's corporate image has a cogent influence between ethical, philanthropic, and sustainable dimensions and organizational performance. The outcomes of preceding literature also demonstrated that CSR initiatives enhance the company's goodwill and images such as Lu et al (2020b), Moliner et al (2019), Suki and Suki (2019), Richard and Zhang (2012), Ahn et al (2020), Singh andSaini (2016), andHan et al (2019).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, a moderator's corporate image has a cogent influence between ethical, philanthropic, and sustainable dimensions and organizational performance. The outcomes of preceding literature also demonstrated that CSR initiatives enhance the company's goodwill and images such as Lu et al (2020b), Moliner et al (2019), Suki and Suki (2019), Richard and Zhang (2012), Ahn et al (2020), Singh andSaini (2016), andHan et al (2019).…”
Section: Discussionmentioning
confidence: 95%
“…The literature has found that the management of the organization adopts CSR as a strategy to enhance its market share. CSR also impacts brand loyalty, and it strengthens company value (Ahn et al, 2020;Han et al, 2019;Khan & Fatma, 2019;Sharma & Jain, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to Ahn et al (2020), the most significant brand equity element is the brand's loyalty and brand image. The researchers used Carroll's (1991) framework to measure corporate social responsibility and Keller's (1993) model to measure its appearance.…”
Section: Brand Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…Loyalty can be understood as customers' personal motivation and drive to re-purchase or re-buy any products or services offered by the same company in the future [1]. Furthermore, the concept of loyalty can also be perceived as the condition in which consumers are willing to re-visit, re-engage or re-communicate with the same company or provider in the future [2] [3].…”
Section: Customer Loyaltymentioning
confidence: 99%